Incidence of nitrogen fertilization and nitrogen/sulfur complementary fertilization on protein accumulation, yield, and end‑use quality of bread wheat cultivars - Arrigoni, Adriana Cecilia; Lazaro, Laura; Rogers, William John; Arata, Agustín Francisco; Tranquilli, Gabriela (Springer, 2025)
Wheat quality is determined by genotype, environment, and genotype x environment interaction. The glutenin and gliadin protein composition are determinants of potential end-use quality. This study evaluated the influence on storage protein accumulation, dough quality, and yield of early fertilization with N and complementary fertilization with N and S. Two field experiments were carried out using six Argentinean wheat genotypes grown under the following fertilization treatments: Control, Nitrogen, and NS foliar complementary fertilization. Spike samples were harvested at different times during the grain-filling stage to quantify the protein fractions and, at maturity, to evaluate grain yield and quality. Higher yields were obtained under fertilization treatments, although the NS treatment did not show a significantly higher result than the N treatment. The grain yield was associated with the grain number. m− 2 (R2 = 0.92). High molecular weight glutenin subunits (HMW-GS) accounted for between 10.5 and 37.9% of total gluten proteins. In the better genotype, dough strength (W) was 323 10−4 J in the control treatment and more than 470 10–4 J in the fertilized treatments. Only HMW-GS accumulation differed between fertilization treatments. Flour quality was associated with HMW-GS composition and Glu-1 quality score values, and not with yield. It would be possible through management of the wheat crop to obtain grains that provide good flour quality, including agronomic practices such as correct choice of the genotype with good HMW-GS composition, and adequate fertilization with N and S.